Estágio Profissional "O ano dos "Superpoderes" de uma Professora Estagiária" - Alexandra Maria Moreira Cunha (2019)
The Professional Internship represents the culmination of all academic training, where the student is confronted with reality. It is during this school year that all the knowledge acquired over the years of teaching will be put into practice and practice, thus building the self, in which we will finally understand what kind of teacher we are and what models and teaching strategies that We identify more through the many challenges and experiences. This document aims to report the year of internship of the student intern, where she was responsible for a class and all decisions regarding the planning, completion and evaluation of teaching. This report is organized into four chapters: the first concerns the "Introduction" where I explain what will be referred to throughout the document; the second, "Biographical Framework: How it all started", gives a short presentation of my sports, professional, academic experiences and expectations for this year and this profession; Then the "Institutional Framework" portrays the professional internship at the institutional, legal and functional level, as well as the presentation of the NE and the analysis of the context where the student-student practice took place; The fourth, "Operational Framework", encompasses the three student-trainee performance areas, including the sub-themes of teaching preparation, completion, and assessment, and the presentation of different school activities. In area three is the research study on "Physical Education Beyond School". This step was the realization of a dream and the preparation for the real world.